Kesehatan telinga siswa Sekolah Dasar Inpres 1073 Pandu - Demmasabu, Sylvester B.; Palandeng, Ora I.; Pelealu, Olivia C. (e-CliniC, 2016)
Abstract: Ear is very important in hearing and balancing. This study aimed to obtain the ear health status of students of Inpres 10/73 Elementary School at Pandu. This was a descriptive observational study with a cross sectional design. Subjects were students of 10/73 Pandu Elementary School. The results showed that from the 18 respondents of this study there were 8 male and 10 female students. The examination of earlobe resulted in all (100%) students had normal ear lobes. The ear canal examination showed that 88.89% of students had normal ear canals, and 11.11% of students had cerumen. The examination of tympanic membranes showed that 61.11% of students had normal tympanic membrane, meanwhile 38.89% of students had perforated or retracted tympanic membrane. Conclusion: Most of the students had normal ear health status, Keywords: ear health, ear examination Â  Abstrak: Telinga adalah organ tubuh yang berperan penting pada proses pendengaran dan keseimbangan. Penelitian ini bertujuan untuk mengetahui gambaran kesehatan telinga pada siswa-siswi SD Inpres 10/73 Pandu. Jenis penelitian ini deskriptif observasional dengan pendekatan potong lintang. Sampel penelitian ialah siswa-siswi kelas V SD Inpres 10/73 Pandu. Jumlah responden 18 siswa/i terdiri dari 8 anak laki-laki dan 10 anak perempuan. Pada pemeriksaaan daun telinga didapatkan 100% normal. Pada pemeriksaan liang telinga didapatkan 88,89% normal dan 11,11% terdapat serumen. Pada pemeriksaan membran timpani persentase normal 61,11% dan persentase anak yang terdapat perforasi dan retraksi 38,89%. Simpulan: Sebagian besar siswa/i mempunyai kesehatan telinga normal. Kata kunci: kesehatan telinga, pemeriksaan telinga